The BaeSR regulon is involved in defense against zinc toxicity in E. coli - Wang, Da (2013)
Intracellular zinc homeostasis is regulated by an extensive network of transporters, ligands and transcription factors. The zinc detoxification functions of three transporters and a periplasmic protein regulated by the BaeSR two-component system were explored in this work by evaluating the effect of single gene knockouts in the BaeSR regulon on cell growth rate, free zinc, total zinc and total copper after zinc shock. Two exporters, MdtABC and MdtD, and the periplasmic protein, Spy, are involved in zinc detoxification based on the growth defects at high cell density and increases in free (>1000-fold) and total zinc/copper (> 2-fold) that were observed in the single knockout strains upon exposure to zinc. These proteins complement the ATP-driven zinc export mediated by ZntA in E. coli to limit zinc toxicity. These results highlight the functions of the BaeSR regulon in metal homeostasis.